An algorithm for restricted normal form to solve dual type non-canonical linear fractional programming problem - Hossain, Mozzem; Morshed, Monjur; Uddin, Mohammad Forhad (BRAC University, 2010)
In this paper, an algorithm is presented to solve non-canonical linear fractional programming (LFP) problem, considering the restricted normal form. It provides a new way to solve all types of LFP problems. When the LFP problem is only in canonical form, Forhad et al. [13] derived an algorithm considering the restricted normal form. In this paper, the algorithm of Forhad et al. [13] has been generalized to solve the LFP problem which is non-canonical form also. This algorithm required neither transformation nor the iterative calculations of simplex method. But it requires only algebraic elimination.